“Spring Cleaning”: Skill-sharing towards conscious clothing consumption - Gorniak, Kasia; Niinimäki, Kirsi (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
This article discusses the case study of “Spring Cleaning”, a one-off event comprising workshops sharing different approaches on extending the use-time of clothing and textiles. Through a qualitative approach, the study aimed to explore if a one-off event can have an impact on the application of skills learnt and how social connectivity contributes to that aim. A secondary aim was to determine if there was a demand for future iterations of this kind of event, in or beyond the university setting. Through the diversity of workshops offered, the event aimed to open up what the parameters of repair, reuse and revival in the clothing and textile sector can be, drawing attention to various timely topics through discussion and practice. These included the preservation of repair skills, celebrating the aesthetics associated with repair and fostering more caring, longer-term relationships with the material world.The findings, gathered through participant observation, a survey and follow-up questionnaire with both participants and facilitators, indicated that for the most part, the event had a positive and lasting impact on attitudes and behaviours around skill-sharing as well as benefits on the social and emotional sides. The sense of opportunity, fulfilment and inspiration was felt from all involved, regardless of their role. Limitations came in the one-off nature of the event, the participant demographic largely having previous experience in clothing or textile repair and in the amount of participant responses only accounting of one third of the total.